Learning innovation on Mechanical Engineering vocational education in the new normal era - Puteri Anggieta Cahyani; Widarto Widarto; Olivia Laras Sati (Jurnal Pendidikan Vokasi, 2021)
This study aims to explore the implementation of vocational learning in the new normal era related to the content, assignment forms, class management, and describe teacher innovations and hope. The research was conducted using a quantitative descriptive approach with a research instrument is a questionnaire. The questionnaire was given to 46 respondents consisting of mechanical engineering vocational teachers from several regions in Indonesia. The questionnaire consists of two categories, namely statements with an option and statements with open answers. The findings of this study are based on two categories, namely theoretical and practical learning. The results reveal that in theory learning, teachers prefer to share material with students in various forms, including PDF, PPT, Video, and others (17.56%), assigning forms in summarizing material (25.19%), and with the full class (47.78%). In contrast, in practical learning, the teacher conducted learning with a system block (5.85%), gave assignments in the form of making projects or products (6.93%), and with half-class management combined with online classes (7.78%). Another finding is the innovation applied by teachers is developing technology-based learning materials and using online platforms. In the new era's learning situation, normal teachers expect a flexible curriculum, as well as standardized, effective, and efficient media, models, methods, and learning platforms. In the learning practice, the teacher expects practice videos and simulation applications that are expected to be by following the expected basic competencies and being equipped with learning practices with the application of health protocols and students' numbers.